Struktuur en boodskap(pe) in die boek Daniël - Deventer, Hans J. M. van (HTS teologiese studies, 2003)
Structure and message(s) in the book of DanielThe book of Daniel presents a number of challenges that scholars have not yet been able to solve. This article focuses on the problem related to the bilingual character of the book of Daniel (Hebrew and Aramaic) and the fact that the two languages do not correspond with the two literary types found in the book (court tales and visions). From a structural perspective this phenomenon is utilised to indicate specific accentuated sections in the book of Daniel. On the basis of these findings, suggestions are made regarding messages in the book. These suggestions combine historical and literary approaches to the text.